Effectiveness of Vaccination against Pneumococcal Infection in Uzbekistan: a Preliminary Assessmant and Prognosis - T. A. Daminov; L. N. Tuychiev; N. U. Tadjieva; N. Kh. Otamuratova (Детские инфекции (Москва))
The article is devoted to questions of vaccination against pneumococcal infection in Uzbekistan. Since November 2015, the vaccination against pneumococcal infection with conjugated pneumococcal vaccines of children 1 year of age at the age of 2, 3, 12 months was introduced to the National Schedule of Immunization program of Uzbekistan. The article presents preliminary results of vaccination effectiveness to reduce hospitalizations of patients with pneumococcal diseases.